2003
DOI: 10.1097/00001721-200306001-00011
|View full text |Cite
|
Sign up to set email alerts
|

New insights into haemostasis in liver failure

Abstract: The precise mechanisms leading to the coagulopathy of acute liver injury are unclear. To study this further, coagulation and immune changes have been compared in patients with acute liver injury secondary to paracetamol overdose, with chronic cirrhosis, and normal healthy controls. In acute liver injury, coagulation factors II, V, VII and X were reduced to a similar degree, and were significantly lower than factors IX and XI. In cirrhosis, by contrast, these coagulation factors were reduced to similar levels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 5 publications
3
35
0
1
Order By: Relevance
“…it was reported that the levels of IL-6 are elevated in liver injury patients, as well as in mice and rats with induced liver damage [15][16][17]25]. iL-6 levels are thus considered to be affected by factors other than liver damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…it was reported that the levels of IL-6 are elevated in liver injury patients, as well as in mice and rats with induced liver damage [15][16][17]25]. iL-6 levels are thus considered to be affected by factors other than liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…high-dose administration of acetaminophen is known to induce hepatopathy [1,15]. bruck et al reported that hepatopathy is induced by a one-time administration of acetaminophen at 1 g/kg in rats [2].…”
Section: Animal Experimentsmentioning
confidence: 99%
“…These levels are affected by acute clotting and other disease processes and there is no clear relationship to bleeding or clotting risks in cirrhosis patients; also shows significant laboratory variations and are expensive. Euglobulin lysis time is a validated measure of fibrinolysis and can be used as a measure of treatment efficacy in hyperfibrinolysis, but is not widely available [29].…”
Section: Common Laboratory Tests For Coagulation In Liver Diseasementioning
confidence: 99%
“…FVII deficiency develops in 75% -85% of patients, and levels range from 23% to 74% of normal in compensated cirrhosis [4]- [7]. FVII levels are significantly lower in decompensated cirrhosis, but 30% of normal ones are in most patients with stable disease [4] [5] [8].…”
Section: Introductionmentioning
confidence: 99%
“…Another possible mechanism of elevated vWF in cirrhosis is induction of synthesis of vWF in the liver with cirrhosis itself [8] or reduced liver-mediated clearance. Although it is established that vWF antigen levels are increased in patients with cirrhosis, relatively little is known on the relation between it and the bleeding from esophageal varices [9] [10] so we aimed in this study to determine the clinical predictors of bleeding esophageal varices and study the role of FVII and vWF in predicting bleeding in patients with eosphogeal varices.…”
Section: Introductionmentioning
confidence: 99%